Examining the Prevalence and Associated Factors of Sexually Transmitted Infections in People Living With HIV/AIDS at a Community Health Center in Bandung City, Indonesia - Nuraeni S; Alfian SD; Puspitasari IM (HIV/AIDS: Research and Palliative Care)
Sani Nuraeni,1,* Sofa Dewi Alfian,2,3 Irma Melyani Puspitasari2,3,* 1Master of Pharmacy Program, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, Indonesia; 2Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, Indonesia; 3Center of Excellence for Pharmaceutical Care Innovation (PHARCI), Universitas Padjajdjaran, Sumedang, Indonesia*These authors contributed equally to this workCorrespondence: Irma Melyani Puspitasari, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, Indonesia, Tel +62 22 84288888 Ext 3510, Email irma.melyani@unpad.ac.idPurpose: This study aims to investigate the prevalence of sexually transmitted infections (STIs) and associated factors among people living with human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS) (PLWHA) registered in a community health center (CHC) with HIV/AIDS support and treatment services in Indonesia.Methods: A cross-sectional study that included all PLWHA data from medical records registered in a CHC with HIV/AIDS support and treatment services was conducted in Bandung City, Indonesia, between March 2019 and March 2024. This CHC provides comprehensive and continuous HIV/AIDS services, including HIV testing, antiretroviral therapy (ART), and opportunistic infection management. The factors associated with the prevalence of STIs in PLWHA, including sociodemographic factors such as gender, age, education level, marital status, occupation, population group, referral origin, and clinical factors such as length of illness, duration of ART, clinical stage, and comorbidities, were analyzed by using chi-square analysis.Results: Total 156 PLWHA data with STIs from medical records were collected (male, n = 152, 97.4%; female, n = 4, 2.6%). The prevalence of STIs among PLWHA was 32.1%, consisting of syphilis (n = 36; 72%), gonorrhea (n = 11; 22%), genital herpes (n = 2; 4%), and condyloma (n = 1; 2%). The following significant factors associated with the prevalence of STIs were population group men who have sex with men (MSM) (p = 0.046), referral origin from non-government organizations (NGOs) (p = 0.030), duration of disease (p = 0.023) and duration of ART ranging from 12 to 36 months (p = 0.023), and early clinical stage (p = 0.010).Conclusion: STIs affected over one-third of CHC-registered PLWHA, with syphilis being the most common. MSMs and patients referred by NGOs, with illness and treatment durations ranging from 12 to 36 months, as well as the early clinical stage of HIV, are associated with STIs among PLWHA. Intervention strategies to improve STI prevention and control in these populations are urgently needed.Keywords: STIs, HIV/AIDS, prevalence, CHC, PLWHA